2006
DOI: 10.1002/ab.20152
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐aggression expectancies and dispositional aggression moderate the relationship between alcohol consumption and alcohol‐related violence

Abstract: Alcohol consumption increases aggression, but only in some drinkers. This study examines how expectancies for alcohol-induced aggression and dispositional aggression moderate the link between alcohol consumption and alcohol-related violence, building on previous studies that have employed limited measures of alcohol-related violence and included few women. A sample of 212 men and women reported their alcohol consumption, alcohol-aggression expectancies, dispositional aggression, and incidents of alcoholrelated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 50 publications
5
48
3
Order By: Relevance
“…It is possible that this expectancy was linked specifically to aggressive problems, both within the marriage as well as with friends, family, and others. For example, Barnwell, Borders, and Earleywine (2006) found that alcohol expectancy for aggression was cross-sectionally associated with aggressive behaviors among heavy drinkers. However, it should be noted that to date, the available evidence does not support a longitudinal association between expectancies and aggression (Quigley & Leonard, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this expectancy was linked specifically to aggressive problems, both within the marriage as well as with friends, family, and others. For example, Barnwell, Borders, and Earleywine (2006) found that alcohol expectancy for aggression was cross-sectionally associated with aggressive behaviors among heavy drinkers. However, it should be noted that to date, the available evidence does not support a longitudinal association between expectancies and aggression (Quigley & Leonard, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have suggested stratifying crime reports to strengthen model or analysis results [1,4,15,23,24,[61][62][63], since consumption increases during the weekend nights [64]. Disorder and assaults were chosen as the focus crime types such that alcohol is known to increase aggression [18] and cause impaired judgment [17] that can lead to violent and disorderly behavior. Crime occurrences were geo-coded to 100 block address at a 98% match success rate, with an average of 97% accuracy.…”
Section: Covariatesmentioning
confidence: 99%
“…We also used the 2011 census count of males between 19 and 24 years old, and the median age per DA to signify populations at risk of alcohol attributable-crime. Young males are documented to consume more alcohol [57], and have a higher probability of experiencing harms such as violence while intoxicated [18,[74][75][76].…”
Section: Count Of Lighting Structures Per Da Lightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Holding alcohol expectancies for aggression may, in some situations, actually increase the likelihood that individuals will behave aggressively when drinking (Quigley and Leonard, 2006). Indeed, studies have shown that alcohol aggression expectancies are positively associated with engaging in alcohol-related aggressive behaviors (e.g., Barnwell et al, 2006).…”
mentioning
confidence: 99%